EXTRACTION OF STRONTIUM(II) BY CROWN ETHER: INSIGHTS FROM DENSITY FUNCTIONAL CALCULATION - Saprizal Hadisaputra; Harno Dwi Pranowo; Ria Armunanto (Universitas Gadjah Mada, 2012)
The structures, energetic and thermodynamic parameters of crown ethers with different cavity size, electron donating/withdrawing substituent groups and donor atoms have been determined with density functional method at B3LYP level of theory in gas and solvent phase. Small core quasi-relativistic effective core potentials was used together with the accompanying SDD basis set for Sr2+ and DZP basis set was used for crown ether atoms. Natural bond orbital (NBO) analysis was evaluated to characterize the distribution of electrons on the complexes. The interaction energy is well correlated with the values of Strontium charge after complexation, the second order interaction energies (E2) and HOMO-LUMO energy gab (∆Egab). The interaction energy and thermodynamics parameters in gas phase are reduced in solvent phase as the solvent molecules weaken the metal-crown ether interaction. The thermodynamic parameters indicated that less feasibility to extract Sr2+ ion directly from pure water without presence of organic solvent. The theoretical values of extraction energy for Sr(NO3)2 salt from aqueous solution in different organic solvent is validated by the experimental trend. This study would have strong contribution in planning the experiments to the design of specific host ligand and screening of solvent for extraction of metal ion.